2007
DOI: 10.1532/ijh97.e0625
|View full text |Cite
|
Sign up to set email alerts
|

Outcome and Prognostic Factors in Patients with Hematologic Malignancies Admitted to the Intensive Care Unit: A Single-Center Experience

Abstract: Patients who are admitted to the intensive care unit (ICU) with hematologic malignancies have a poor prognosis, although outcomes have improved in recent years. This study analyzed ICU mortality, short- and long-term survival, and prognostic factors for 100 consecutive critically ill patients with a hematologic malignancy who were admitted to our polyvalent ICU from January 2000 to May 2006. The median age was 55 years (range, 15-75 years; male-female ratio, 60:40). The main acute life-threatening diseases pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
40
4
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 29 publications
11
40
4
2
Order By: Relevance
“…Mean survival in the present study was lower than that previously reported, [29,30] and may have been due to several factors, including late presentation to hospital or a shortage of chemotherapeutic drugs. Improve outcome was reported for patients with early presentation and early stages of disease.…”
Section: (100) Totalcontrasting
confidence: 94%
“…Mean survival in the present study was lower than that previously reported, [29,30] and may have been due to several factors, including late presentation to hospital or a shortage of chemotherapeutic drugs. Improve outcome was reported for patients with early presentation and early stages of disease.…”
Section: (100) Totalcontrasting
confidence: 94%
“…2,3,5,6 In that setting, mortality may reach 60 -90%. 7 Other factors associated with mortality were worse performance status on the Eastern Cooperative Oncology Group/World Health Organization scale, 8 allogeneic stem cell transplantation, high organ failure scores, increased organ dysfunction throughout the ICU stay, as well as diagnosis of invasive pulmonary aspergillosis. 2,4,9-13 ARF may be related to various etiologies, and failure to identify the cause is associated with increased mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Survival rates may be increasing however since recent data demonstrate hospital and one year survival of 54-60% and 43%, respectively [9,10]. Outcomes after haemopoeitic stem cell transplantation (HSCT) appear to be worse [11], although there have been a number of papers suggesting that the prognosis may have improved even among HSCT recipients [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%